Flags on the bayou : a novel [compact disc, unabridged] - Burke, James Lee, 1936- (Simon & Schuster Audio, 2023)
In the fall of 1863, the Union army is in control of the Mississippi river. Much of Louisiana, including New Orleans and Baton Rouge, is occupied. The Confederate army is retreating toward Texas, and being replaced by Red Legs, irregulars commanded by a maniacal figure, and enslaved men and women are beginning to glimpse freedom. When Hannah Laveau, an enslaved woman working on the Lufkin plantation, is accused of murder, she goes on the run with Florence Milton, an abolitionist schoolteacher, dodging the local constable and the slavecatchers that prowl the bayous. Wade Lufkin, haunted by what he observed-and did-as a surgeon on the battlefield, has returned to his uncle's plantation to convalesce, where he becomes enraptured by Hannah.